FRAILTY AND AGE-RELATED CONDITIONS AMONG WORLD TRADE CENTER GENERAL RESPONDERS. (20th December 2022) - Ornstein, Katherine; Ko, Fred; Park, Amy; Sabra, Ahmad; Ferreira, Katelyn; Hung, William; Lucchini, Roberto; Thanik, Erin
Abstract: As WTC exposure may precipitate frailty, we examined patterns of frailty in the general responders cohort. We used two methods to assess frailty: a Clinical Frailty Index (FI) developed using a deficit accumulation approach utilizing clinical assessments performed during routine annual visits to a WTC clinical program in New York City; and a frailty questionnaire (5-point FRAIL scale) collected from a subsample of responders. Using a Clinical FI cutoff score of 0.25, over 25% of the 7, 679 participants, median age 58.3 years (IQR 9.3), who had any visit to the WTC clinical program from 2017 to 2019, were frail. In a subsample of 100 participants with additional frailty assessment (FRAIL scale), we found that 27% were pre-frail, 5% were frail, 14% had recent falls, 9% had ADL dependencies; 34% had mild cognitive impairment. These data suggest that frailty and its related conditions are prevalent among the cohort despite younger age.